2017
DOI: 10.3390/ijerph14101264
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Resources at the Workplace with Health-Promoting Leadership

Abstract: Leaders engaging in health-promoting leadership can influence their employees’ health directly by showing health awareness or indirectly by changing working conditions. With health-promoting leadership, leaders are able to support a healthy working environment by providing resource-oriented working conditions for their employees to support their health. Changing working conditions in a health-supportive way can prevent possible negative consequences from critical working conditions (e.g., burnout risk). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…Athletes with more autonomy-supportive environments also felt less anxious and burned-out [27]. Recent studies in non-sport settings also showed consistent results that perceptions of leaders’ and supervisors’ support significantly predicted burnout [11,28]. Vealey and colleagues [15] examined the effect of athletes’ perceptions of coaching behaviors on burnout and competitive anxiety and also tested the relationship between athletes’ levels of competitive (trait) anxiety and burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Athletes with more autonomy-supportive environments also felt less anxious and burned-out [27]. Recent studies in non-sport settings also showed consistent results that perceptions of leaders’ and supervisors’ support significantly predicted burnout [11,28]. Vealey and colleagues [15] examined the effect of athletes’ perceptions of coaching behaviors on burnout and competitive anxiety and also tested the relationship between athletes’ levels of competitive (trait) anxiety and burnout.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between supervisor and subordinate is an important determinant of partnership processes [ 25 ] and a healthy workplace [ 32 ]. Leader behavior can buffer the effect of envy on CWB [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows that more than two-thirds (68.5%) of the nurse educators engaged in the health risky overburdened pattern of work, whereas only 13.8% reported engaging in the maladaptive burnout pattern. Engagement in the healthy pattern was observed in 16.2% of the nurse educators. A particularly small percentage (1.5%) of respondents had adopted the frugal pattern of behavior.…”
Section: Sample Demographic and Academic Characteristicsmentioning
confidence: 99%
“…An increasing number of researchers have investigated the types of resources and/or coping mechanisms that promote adaptation at work. [16,17] Sense of coherence is an important internal psychological resource that facilitates stress management, and contributes to a sense of well-being. [18][19][20][21] According to Antonovsky (1979, cited by Oosthuizen and Vanlill) sense of coherence, as a dispositional orientation toward life, is captured by three dimensions: comprehensibility, manageability, and meaningfulness.…”
Section: Introductionmentioning
confidence: 99%